(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The safety of participants in criminal proceedings has become a paramount concern across jurisdictions, especially in cases involving organized crime, terrorism, or vulnerable witnesses. While protective measures such as anonymity, witness relocation, and special interrogation techniques are essential, they often raise complex questions regarding the admissibility and reliability of evidence obtained under such circumstances. This article examines the legal standards and practices concerning the admissibility of evidence collected during protective procedures, with a focus on comparative developments in the United States, the United Kingdom, the European Union, and international criminal law. Through an analysis of landmark cases and legislative frameworks, the article identifies emerging trends, legal dilemmas, and potential safeguards to ensure both fair trial rights and the protection of justice system participants.